Assessing the Satisfaction and Acceptability of an Online Parent Coaching Intervention: A Mixed-Methods Approach - Qu, Lu; Chen, Huiying; Miller, Haylie; Miller, Alison; Colombi, Costanza; Chen, Weiyun; Ulrich, Dale A. (Frontiers in Psychology, 2022)
Background: Parent-mediated intervention has been studied in promoting skill acquisition or behavior change in the children with autism spectrum disorder. Most studies emphasize on the improvement of child's core symptoms or maladaptive behaviors, making parental perceived competence and self-efficacy secondary. Yet, the evaluations of implementation-related outcomes of such interventions are under-reported compared to the intervention success, especially when translating into a new population. In mainland China, health insurance coverage, parents' time limits, and geographical barriers prevent parents from accessing to parent training services. This research investigated the telehealth delivery for a 12-week parent coaching intervention based on parent-mediated Early Start Denver Model with culturally adapted lectures, manuals, and demonstration and commentary videos. This study aimed to evaluate Chinese parents’ satisfaction and acceptability on participation in a culturally adapted parent coaching intervention via telehealth. Method: This mixed-methods study used a concurrent convergent design to evaluate post-intervention data from a randomized controlled feasibility trial. The treatment group (Web + group therapy) navigated the same website as the active comparison group (self-directed) with an additional 1.5 hours of group coaching therapy weekly. The quantitative data was collected from the Program Evaluation Survey and the qualitative data was collected from five focus groups. Results: Parents in self-directed group reported significantly lower scores in total perceived competence than parents in Web + group therapy group, while there was no group difference on the total self-efficacy. Tailored feedback, demonstration and commentary videos, peer commenting, live coaching, and guided reflection were top-five acceptable telehealth strategies that were strongly endorsed by parents. Family-centered care, home-based intervention, strategies relative to daily activities, the remote learning platform, and the program-based community were elements that parents considered when evaluating the program's appropriateness. Parent modelling, step-by-step instructions, and tailored feedback were key components in making intervention strategies feasible for parents to implement at home. Conclusions: Findings indicate the application of telehealth was acceptable, appropriate, and feasible for Chinese parents. Group-based parent coaching intervention via videoconferencing could be a promising home-based service model to increase parental perceived competence. A large-scale RCT is needed to investigate the effectiveness of group-based PMI via telehealth.